Rancang Bangun Aplikasi Augmented Reality Museum Bali Berbasis Android Studi Kasus Gedung Karangasem dan Gedung Tabanan - Aditya Nugraha, I Gede; Putra, I Ketut Gede Darma; Sukarsa, I Made (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 7, No. 2 Agustus 2016, 2016)
Museum Bali is one of the museum which is located in Denpasar City that established since 1910. The Museum collections consist of items such as living equipment, art, religion, handwriting, and other things that show the situation and the development of the Balinese culture. Augmented Reality is a technology which combines two-dimensional virtual objects or three-dimensional virtual objects into the real environment. Museum Bali has decreased the amount of visitors in recent years and requires an innovation to promote Museum Bali. One innovation that is expected to promote the Museum Bali is to create an augmented reality application that called Augmented Reality Museum Bali in Android platform. Utilizing augmented reality technology that works by detecting the marker then it show up the 3D object and the information from one of the objectsin Museum Bali. Markerless method used in detection marker that make this application moreattractive and expected to be a new experience for the people who want to know more about Museum Bali.
Keywords: Museum Bali; Augmented Reality; Android; Marker